On the Link between Exchange-Rate Regimes and Monetary-Policy Autonomy: The European Experience - Jens Forssbæck; Lars Oxelheim (The Research Institute of Industrial Economics (IUI), 2005)
We investigate monetary-policy autonomy under different exchange-rate regimes in small, open European economies during the 1980s and 1990s. We find no systematic link between ex post monetary-policy autonomy and exchange rate regimes. This result is enforced for countries/periods with alternative nominal targets. Our interpretation of the results is that over the medium and long term following an independent target for monetary policy, which does not deviate much from the targets of those countries to which one is closely financially integrated, is as constraining as locking the exchange rate to some particular level
Keywords: E42; E52; F41; 330; Exchange Rate Regimes; Monetary Policy Autonomy; Capital Mobility; Wechselkurssystem; Geldpolitik; Eurozone; Kapitalmobilität; Kleine offene Volkswirtschaft; Schätzung; Westeuropa